Evaluating Jail Readmission Risk With a Nine-Item Behavioral Health Screen. Issue 3 (27th May 2019) - Kopak, Albert; Hoffmann, Norman; Guston, Kaitlin
ABSTRACT: Evidence shows substance use disorders and mental health conditions are linked to an increased probability of jail readmission, but many local facilities do not have the resources to conduct comprehensive behavioral health assessments. This prospective longitudinal study examined the utility of a nine-item screen to identify adults with a high probability of readmission. Results from a sample of 255 adults booked into a local county jail demonstrate that this brief index can classify adults with accuracy rates similar to those of significantly longer instruments. Multivariate logistic regression analyses also indicate the index is significantly associated with the risk of 12-month jail readmission.